GAMIFICATION-BASED APPS IN TEACHING AND LEARNING ENGLISH: A SYSTEMATIC LITERATURE REVIEW - SITUMORANG, KOMILIE (Universitas Lambung Mangkurat, 2023)
The use of gamification-based apps has gained popularities in the last few years as teachers were forced to be creative in designing the teaching and learning activities during the pandemic. This study is a Systematic Review using Prism methodology which aims to seek what gamification-based apps have been researched, methodologies, targets, years, and areas improved. The research resulted in 28 papers associated with the research topic collected from a single database i.e., Google Scholar. The results were synthesised in tables and figures based on the questions and discussed thoroughly. The research highlights the main findings include Quizziz as most used gamification apps, Quantitative approach as most popular research method, most targeted participants were senior high school, most studies were done in 2021, and engagement was the most improved aspect through the utilisation of gamification-based apps. The study also proposes some recommendations for the future research including the limitation of the study.